FRI0429 What Is The Location of Dactylitis in Ankylosing Spondylitis and Psoriatic Arthritis Patients and How Do They Respond To Anti-TNF Treatment?. (15th July 2016) - Arendse, R.; Rahman, P.; Avina-Zubieta, J.A.; Choquette, D.; Zummer, M.; Baker, M.; Stewart, J.; Fortin, I.; Teo, M.; Rampakakis, E.; Psaradellis, E.; Osborne, B.; et al.
Abstract : Background: Dactylitis is one of the most commonly reported features in spondyloarthritis. It has been hypothesized that dactylitis is a functional enthesitis at the proximal interphalangeal joints, resulting in synovitis, tenosynovitis, bone and soft tissue oedema to the digit, and may simultaneously involve more than one digit. Objectives: Our objective was to identify the location of dactylitis in ankylosing spondylitis (AS) and psoriatic arthritis (PsA) patients and to determine their response to anti-TNF treatment. Methods: BioTRAC is an ongoing, prospective registry of patients initiating treatment for rheumatoid arthritis (RA), ankylosing spondylitis (AS), or psoriatic arthritis (PsA) with infliximab (IFX) or golimumab (GLM). Eligible people for this analysis included AS and PsA patients treated with IFX who were enrolled since 2005 or with GLM enrolled since 2010 who had available information on dactylitis. The McNemar (paired Chi-square) test was used to compare the presence of dactylitis over time. Results: A total of 260 AS patients and 261 PsA patients were enrolled with a mean (SD) age at baseline of 46.1 (13.0) vs. 50.0 (12.0) years, disease duration of 6.4 (9.8) vs. 5.2 (6.8) years, and proportion of females 40.6% vs. 48.5%, respectively. Among patients with AS, dactylitis was reported in 6.2% and 2.2% of patients at baseline and 6 months, respectively; at 6 months of treatment 73.3% of AS patients with dactylitis at baseline had no dactylitis and 1.6% developed dactylitis (P=0.057). For PsA higher proportions of dactylitis were observed with 30.7%, and 12.7%, respectively; at 6 months of treatment 69.0% of PsA patients with dactylitis at baseline had no dactylitis and 4.6% developed dactylitis (P<0.001). The distribution of dactylitis amongst digits is described in Table 1 with the highest prevalence observed for feet in AS and PsA patients. Presence of dactylitis in hands or feet (any digit) was associated with significantly higher HAQ in AS and PsA (AS: ΔHAQ=1.36 (P≤0.001); PsA: ΔHAQ=0.64 (P≤0.001)). Conclusions: A considerable proportion of PsA patients had dactylitis at anti-TNF initiation in this Canadian real-world cohort. Although a lower proportion of patients had dactylitis among AS patients, the presence of dactylitis was associated with higher functional disability in both AS and PsA patients. Treatment with IFX or GLM for 6 months was associated with significant reduction in the prevalence of dactylitis. Disclosure of Interest: R. Arendse: None declared, P. Rahman: None declared, J. A. Avina-Zubieta: None declared, D. Choquette: None declared, M. Zummer: None declared, M. Baker: None declared, J. Stewart: None declared, I. Fortin: None declared, M. Teo: None declared, E. Rampakakis: None declared, E. Psaradellis: None declared, B. Osborne Employee of: Janssen Inc. Canada, C. Tkaczyk Employee of: Janssen Inc. Canada, K. Maslova Employee of: Janssen Inc. Canada, F. Nantel Employee of: Janssen Inc. Canada, A. Lehman Employee of: Janssen Inc. Canada